Comparison of Nitric Oxide Concentrations in μs- and ns-Atmospheric Pressure Plasmas by UV Absorption Spectroscopy. (April 2016) - Peters, F.; Hirschberg, J.; Mertens, N.; Wieneke, S.; Viöl, W.
Abstract: In this paper, an absorption spectroscopy measurement method was applied on two atmospheric pressure plasma sources to determine their production of nitric oxide. The concentrations are essential for evaluating the plasma sources based on the principle of the Dielectric Barrier Discharge (DBD) for applications in plasma medicine. The described method is based on a setup with an electrodeless discharge lamp filled with a mixture of oxygen and nitrogen. One of the emitted wavelengths is an important resonance wavelength of nitric oxide (λ = 226.2 nm). By comparing the absorption behaviour at the minimum and maximum of the spectral absorption cross section of nitric oxide around that wavelength, and measuring the change in intensity by the absorbing plasma, the concentration of nitric oxide inside the plasma can be calculated. The produced nitric oxide concentrations depend on the pulse duration and are in the range of 180 ppm to 1400 ppm, so that a distance of about 10cm to the respiratory tract is enough to conform to the VDI Guideline 2310.